Inspiratory muscle training in natural bodybuilders: adaptations in diaphragm muscle thickness and maximal strength - Güler, Iskender; Yılmaz, Coşkun; Soylu, Hakan Hüseyin; Birinci, Mürşit Ceyhun; Arslan, Ayla; Ocak, Hakan; Çayir, Hüseyin; Kavuran, Korhan; Saç, Ajlan; Akkuş Uçar, Mine; Karataş, Baykal; Ceylan, Levent (Frontiers in Physiology, 2025)
BackgroundThe effect of inspiratory muscle training on diaphragm muscle thickness (DT) and one repetition maximal (1RM) in professional natural bodybuilders is still unclear. The aim of the study was to investigate the effect of inspiratory muscle training on diaphragm muscle thickness and 1RM in professional natural bodybuilders.MethodsThe study comprised a total of 22 athletes who participated in bodybuilding competitions. Each athlete had undergone a minimum of 5 years of training, with a minimum weekly commitment of 5 hours. Participants were randomly divided into two groups: inspiratory muscle training (IMT) and control (CON). The CON continued their normal training regime, while the IMT group also performed inspiratory muscle training with a 10% weekly increase by setting the resistance setting of the PowerBreathe® Classic device to 40% of the participant’s maximum inspiratory pressure (MIP). Prior to and during the 4-week training period, 1RM bench press measurements and diaphragm muscle thickness measurements were obtained.ResultsIn the comparison of 1RM power values before and after training, it was determined that the IMT group (%: 11.20) had 6.3% more post-activation performance enhancement compared to the CON group (%: 4.9) (p < 0.001). In the study, it was determined that a higher level of significant post-activation performance enhancement was obtained in the IMT group compared to the CON group in the diaphragm muscle thickness inspiratory phase (DT ins) and ekspiratory phase (DT eks) parameters at 20.36% and 19.46%, respectively.ConclusionIn conclusion, we determined that the addition of progressive loading inspiratory muscle training to preparation programmes in natural bodybuilders will improve diaphragm muscle thickness, 1RM physical performance. In particular, it shows that the diaphragm muscle should be considered not only as a muscle that supports respiration, but also as a muscle that contributes to power generation by optimising intra-abdominal pressure.